Why Cognitive Sciences Do Not Prove That Free Will Is an Epiphenomenon - Lavazza, Andrea (Frontiers in Psychology, 2019)
Is epiphenomenalism virtually entailed by the current empirical knowledge about how the mind/brain causes human behavior? I’ll address this question by highlighting that recent discoveries in empirical psychology and neuroscience actually do not strike the final blow to the notions of free will and intentional agency. Indeed, most of the experiments that purport to show that our behavior is unconscious and automatic do not prove that it is indeed the case and that therefore we do not have free will. There are many reasons for this, including the fact that those experiments focus on a specific range of our behaviour, one that manifests a significant correlation between unconscious priming and decisions or reactions. However, this doesn’t mean that the entire range of our relevant behavior works the same way. It can be argued that there are situations of higher relevance in which we are fully conscious of our decisions or, at least, there are decisions such that psychological experiments cannot prove them to always be unconscious and automatic. However, the epiphenomenalist challenge may suggest that we should abandon some of the suppositions implied by a traditional idea of free will.